Cloning, overexpression, and purification of functional human purine nucleoside phosphorylase - Silva, Rafael G.; Carvalho, Luiz Pedro S.; Oliveira, Jaim S.; Pinto, Clotilde A.; Mendes, Maria A.; Palma, Mario Sergio [UNESP]; Basso, Luiz A.; Santos, Diógenes S. (My University, 2003)
Purine nucleoside phosphorylase (PNP) catalyzes the phosphorolysis of the N-ribosidic bonds of purine nucleosides and deoxynucleosides. A genetic deficiency due to mutations in the gene encoding for human PNP causes T-cell deficiency as the major physiological defect. Inappropriate activation of T-cells has been implicated in several clinically relevant human conditions such as transplant tissue rejection, psoriasis, rheumatoid arthritis, lupus, and T-cell lymphomas. Human PNP is therefore a target for inhibitor development aiming at T-cell immune response modulation. In addition, bacterial PNP has been used as reactant in a fast and sensitive spectrophotometric method that allows both quantitation of inorganic phosphate (Pi) and continuous assay of reactions that generate P i such as those catalyzed by ATPases and GTPases. Human PNP may therefore be an important biotechnological tool for P i detection. However, low expression of human PNP in bacterial hosts, protein purification protocols involving many steps, and low protein yields represent technical obstacles to be overcome if human PNP is to be used in either high-throughput drug screening or as a reagent in an affordable P i detection method. Here, we describe PCR amplification of human PNP from a liver cDNA library, cloning, expression in Escherichia coli host, purification, and activity measurement of homogeneous enzyme. Human PNP represented approximately 42% of total soluble cell proteins with no induction being necessary to express the target protein. Enzyme activity measurements demonstrated a 707-fold increase in specific activity of cloned human PNP as compared to control. Purification of cloned human PNP was achieved by a two-step purification protocol, yielding 48 mg homogeneous enzyme from 1 L cell culture, with a specific activity value of 80 U mg -1. © 2002 Elsevier Science (USA). All rights reserved.
Keywords: purine nucleoside phosphorylase; recombinant protein; Escherichia coli; gene expression; genetics; human; isolation and purification; metabolism; molecular cloning; polyacrylamide gel electrophoresis; Cloning, Molecular; Electrophoresis, Polyacrylamide Gel; Gene Expression; Humans; Purine-Nucleoside Phosphorylase; Recombinant Proteins; Bacteria (microorganisms)